Effects of Exogenous Application of Phenolic Acid on Soil Nutrient Availability, Enzyme Activities, and Microbial Communities - Yi Zhou; Yihang Liu; Chaoqiang Jiang; Zeinab El-Desouki; Muhammad Riaz; Chenlu Wang; Xueping Zhang; Jiayi Ding; Zhenghao Chen; Huaiwei Liu; Jia Shen; Hao Xia (Agriculture)
Phenolic acids are important allelochemicals that contribute to obstacles in continuous cropping systems, significantly impacting soil nutrients, enzyme activities, and the composition of microbial communities. This study explored the effects of treatment time and the concentration of various phenolic acids (salicylic acid and p-hydroxybenzoic acid) on soil nutrients, enzyme activity, and soil microorganisms through cultivation experiments. The results indicated that high-concentration phenolic acid treatment negatively affected the availability of soil nutrients by acidifying the soil, as reflected in the low soil pH, compared to the untreated control. Moreover, the soil extracellular enzymes exhibited varying degrees of improvement when phenolic acids were added. Multi-element analysis revealed that treatment duration, concentration, and the type of phenolic acid significantly affected soil nutrient levels and enzyme activity. Additionally, structural equation modeling indicated a significant correlation between the concentration of phenolic acids and the diversity of microorganisms. Phenolic acids influence the soil ecological environment by altering the relative abundance of functional microorganisms (p_Patescibacteria and p_Mortierellomycota) in the soil. Thus, comprehensive regulation and control of continuous cropping obstacles can be achieved by adjusting the micro-ecological environment of the soil, which, in turn, affects phenolic acid substances present in the soil, thereby alleviating continuous cropping obstacles.